Successful Treatment of Genetically Profiled Pediatric Extranodal NK/T‐Cell Lymphoma Targeting Oncogenic STAT3 Mutation. Issue 4 (5th January 2016) - McEachron, Troy A.; Kirov, Ivan; Wungwattana, Minkkwan; Cortes, Daisy; Zabokrtsky, Keri B.; Sassoon, Aaron; Craig, David; Carpten, John D.; Sender, Leonard S.
Abstract : Extranodal natural killer (NK)/T‐cell lymphoma (ENKTCL) is a distinct type of non‐Hodgkin lymphoma predominantly observed in Asian and Latin American adult males. A 12‐year‐old Hispanic female diagnosed with ENKTCL was enrolled in our genomic profiling research protocol. We identified specific somatic alterations consistent with diagnosis of ENKTCL as well as oncogenic mutations in MAP2K1 and STAT3 . To our knowledge, this is the first report of an immunophenotypically confirmed and genetically profiled case of ENKTCL in a female pediatric patient in the United States, including its unique treatment and favorable outcome.